Analysis of the kinematic pattern of free throw by wheelchair basketball athletes: a systematic review. - Hugo Vinícius de Oliveira Silva; Karina Santos Guedes de Sá; José Irineu Gorla; Anselmo Athayde Costa E Silva; Dernival Bertoncello (PLoS ONE)
Athletes are stratified into classes that range from 1.0 to 4.5 points subdivided at intervals of 0.5 points in the Wheelchair Basketball (WCB) modality. The discussion regarding the non-utilization of quantitative data based on functional classification (FC) in WCB has become considerably important for research due to its impact on athletes' careers. The aim of this systematic review was to verify the kinematic patterns of the free throw performed by WCB athletes of distinct FC. After researching four online databases, only 7 out of 68 studies fulfilled the inclusion criteria. High-class players (classes 3.0 - 4.5) presented a throw pattern, with a greater angle on the shoulder joint, on the angular speed of the wrist, and the height of the ball throw; low-class athletes (classes 1.0 - 2.5) exhibited a pushing pattern, with greater speed and throw angles, greater angular speed at the shoulder and elbow joints. Thus, inter-individual differences allow for the stratification of players into distinct classes and serve as relevant tools for increasing accuracy and performance despite different disabilities. Further studies are necessary to explore the associated patterns for each FC.